EFEKTIVITAS INSTAGRAM TERHADAP KEPUTUSAN BERKUNJUNG KE DESA WISATA BULUHCINA (STUDI DESKRIPTIF KUANTITATIF TERHADAP AKUN INSTAGRAM @DESABULUHCINA) - Tutut Ismi Wahidar (Jurnal Ilmu Komunikasi, 2019)
The concept of communication established through social media Instagram is by sharing photos and videos along with descriptions of these posts so that they can attract attention to become followers. Users who are already connected can also interact with each other intensely by providing a comment column on the post. Instagram is widely used by travelers as a reference for tourist sites to be visited. One of them is the Instagram account @desabuluhcina which focuses on posting information related to tourism potential in the Tourism Village of Buluhcina, Riau Province. This study aims to describe the effectiveness of Instagram as a promotional medium for the decision to visit the tourist village of Buluhcina. The research method uses quantitative descriptive methods. The population in this study were 165 people (accounts), and 63 samples used the Taro Yamane formula with a precision of 10%. The data collection technique was carried out using questionnaires and observations on the Instagram account @desabuluhcina. The results of this study are based on the results of the calculation of the hypothesis test using the Pearson formula is 0.947 <0.05 and the coefficient of determination of the effectiveness of the Instagram @desabuluhcina account on the decision of visiting tourists is 90%. Then there is a very high influence of 90% between the effectiveness of Instagram on the @desabuluhcina account on the decision to visit the tourist village of Buluhcina.